Bifidobacterium animalis subsp. lactis HN019 live probiotics and postbiotics: production strategies and bioactivity evaluation for potential therapeutic properties - D’ambrosio, Sergio; Dabous, Azza; Sadiq, Saba; Casillo, Angela; Schiraldi, Chiara; Cassese, Elisabetta; Bedini, Emiliano; Corsaro, Maria Michela; Cimini, Donatella (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction:B. animalis subsp. lactis HN019 is a commercially available well-characterized probiotic with documented effects on human health, such as the ability to enhance the immune function and to balance the intestinal microbiome. Therefore, optimizing the manufacturing process to improve sustainability, increasing biomass yields and viability, and avoiding animal -derived nutrients in the medium to meet vegan consumer’s needs, is currently of interest. Besides the established use of live probiotic cells, alternative supplements indicated as postbiotics, like non-viable cells and/or probiotics derived bioactive molecules might be considered as potential next generation biotherapeutics. In fact, advantages of postbiotics include fewer technological limitations, such as easier production processes and scale-up, and even higher specificity. Methods: In this work, medium design together with different fermentation strategies such as batch, fed-batch and in situ product removal on lab-scale bioreactors were combined. Medium pretreatment by ultrafiltration and protease digestion was performed to reduce polysaccharidic contaminants and facilitate the purification of secreted exopolysaccharides (EPS). The latter were isolated from the fermentation broth and characterized through NMR, GC-MS and SEC-TDA analyses. The expression of TLR-4, NF-kb and IL-6 in LPS challenged differentiated CaCo-2 cells treated with EPS, live and heat-killed B. lactis cells/broth, was evaluated in vitro by western blotting and ELISA. Zonulin was also assessed by immunofluorescence assays. Results and Discussion: The titer of viable B. lactis HN019 was increased up to 2.9 ± 0.1 x 1010 on an animal-free semidefined medium by applying an ISPR fermentation strategy. Medium pre-treatment and a simple downstream procedure enriched the representativity of the EPS recovered (87%), the composition of which revealed the presence of mannuronic acid among other sugars typically present in polysaccharides produced by bifidobacteria. The isolated EPS, live cells and whole heat inactivated broth were compared for the first up to date for their immunomodulatory and anti-inflammatory properties and for their ability to promote intestinal barrier integrity. Interestingly, EPS and live cells samples demonstrated immune-stimulating properties by downregulating the expression of TLR-4 and NF-kb, and the ability to promote restoring the integrity of the intestinal barrier by up-regulating the expression of zonulin, one of the tight junctions forming proteins. Postbiotics in the form of heat killed broth only reduced NF-kb expression, whereas they did not seem effective in the other tested conditions.